Changes in utilization of health services among poor and rural residents in Uganda: are reforms benefitting the poor? - Bishai David M; Peterson Stefan; Rahman Mohammed; Okui Olico; Ekirapa-Kiracho Elizabeth; Pariyo George W; Lucas Henry; Peters David H (BMC, 2009)
Abstract Background Uganda implemented health sector reforms to make services more accessible to the population. An assessment of the likely impact of these reforms is important for informing policy. This paper describes the changes in utilization of health services that occurred among the poor and those in rural areas between 2002/3 and 2005/6 and associated factors. Methods Secondary data analysis was done using the socio-economic component of the Uganda National Household Surveys 2002/03 and 2005/06. The poor were identified from wealth quintiles constructed using an asset based index derived from Principal Components Analysis (PCA). The probability of choice of health care provider was assessed using multinomial logistic regression and multi-level statistical models. Results The odds of not seeking care in 2005/6 were 1.79 times higher than in 2002/3 (OR = 1.79; 95% CI 1.65 - 1.94). The rural population experienced a 43% reduction in the risk of not seeking care because of poor geographical access (OR = 0.57; 95% CI 0.48 - 0.67). The risk of not seeking care due to high costs did not change significantly. Private for profit providers (PFP) were the major providers of services in 2002/3 and 2005/6. Using PFP as base category, respondents were more likely to have used private not for profit (PNFP) in 2005/6 than in 2002/3 (OR = 2.15; 95% CI 1.58 - 2.92), and also more likely to use public facilities in 2005/6 than 2002/3 (OR = 1.31; 95% CI 1.15 - 1.48). The most poor, females, rural residents, and those from elderly headed households were more likely to use public facilities relative to PFP. Conclusion Although overall utilization of public and PNFP services by rural and poor populations had increased, PFP remained the major source of care. The odds of not seeking care due to distance decreased in rural areas but cost continued to be an important barrier to seeking health services for residents from poor, rural, and elderly headed households. Policy makers should consider targeting subsidies to the poor and rural populations. Public private partnerships should be broadened to increase access to health services among the vulnerable.